Characterization of the expanded austenite developed on AISI 316 LM steel by plasma nitriding - KEDDAM, MOURAD; Thiriet, TONY; MARCOS, Grégory; Czerwiec, Thierry (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
The samples of AISI 316 LM stainless steel were plasma nitrided at a temperature of 380°C for different times between 0.5 and 8 h in a 85%N2-15% H2 gas mixture. Different experimental techniques such as : optical microscopy (OM), X- rays diffraction (XRD ) and glow discharge optical emission spectroscopy (GDOES) were used to characterize the expanded austenite layer formed on the surface of AISI 316 LM stainless steel. The microscopical observations revealed the presence of the expanded austenite with a mean layer thickness between 1.90 and 4.31 µm. The growth kinetics of expanded austenite was also investigated. In addition, both the compressive stresses in the expanded austenite layer and the compositional strains were estimated by means of a simple mechanical model based on the XRD results.